2012
DOI: 10.1021/am201693e
|View full text |Cite
|
Sign up to set email alerts
|

Wet Air Oxidation of Formic Acid Using Nanoparticle-Modified Polysulfone Hollow Fibers as Gas–Liquid Contactors

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Harikrishnan et al 14 observed a protective effect of resin in fiber reinforced composite materials, blocking corrosive agents from reaching the fibers. However, Hogg et al 15 discovered that acidic media could infiltrate along the fiber‐resin interface in acidic environments, leading to debonding between the resin and fibers. Also, Cunha et al 16 reported that basalt fiber reinforced epoxy composites show better acid resistance than glass fiber reinforced epoxy resin composites.…”
Section: Introductionmentioning
confidence: 99%
“…Harikrishnan et al 14 observed a protective effect of resin in fiber reinforced composite materials, blocking corrosive agents from reaching the fibers. However, Hogg et al 15 discovered that acidic media could infiltrate along the fiber‐resin interface in acidic environments, leading to debonding between the resin and fibers. Also, Cunha et al 16 reported that basalt fiber reinforced epoxy composites show better acid resistance than glass fiber reinforced epoxy resin composites.…”
Section: Introductionmentioning
confidence: 99%
“…In this frame, polymeric catalytic membranes have proven to be outstanding tools for catalytic reactions in the fine chemical industry, generally working under mild conditions (< 150°C) [9][10][11][12]. Efficient catalytic membranes containing metal nanoparticles (MNP) have been reported for different reactions, mainly involving noble metals such as Pd, Au and Ag (CeC coupling reactions [13,14], hydrogenation of nitrates in water [15][16][17], hydrogenation of unsaturated organic compounds [18][19][20][21][22][23][24][25][26][27] including the reduction of 4nitrophenol [28][29][30][31][32], among others). In polymeric catalytic membranes, the catalyst can be incorporated in all the membrane (during or after its synthesis) or in a grafted polymeric layer at the surface of the membrane which stabilized the MNP by steric or electro-steric effect.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of microreaction technology, microchannel reactors provide an excellent opportunity to address the above issues, and a variety of gas-liquid and gas-liquidsolid microchannel reactors has been developed so far (Elvira et al, 2013;Gutmann et al, 2015;Hessel et al, 2005;Jähnisch et al, 2004;Mallia and Baxendale, 2015). Among these, membrane microchannel reactors are an emerging type of reactors for process intensification, which combine the benefits of both membrane reactors and microchannel reactors (Aran et al, 2011a;Aran et al, 2011b;Hogg et al, 2012;Liu et al, 2016;Noël and Hessel, 2013;Selinsek et al, 2016;Tan and Li, 2013). The integration of membrane into a microchannel reactor forces gas and liquid phases to flow separately with a well-defined contacting interface.…”
Section: Introductionmentioning
confidence: 99%